Metal distribution for sediment samples of the cruise AT004 - Catharina Petrauskas; Dominik Wippermann; Tristan Zimmermann; Ole Klein; Daniel Pröfrock (PANGAEA, 2024)
Offshore wind energy is a steadily growing sector contributing to the worldwide energy production. The impact of these offshore constructions on the marine environment, however, remains unclear in many aspects. In fact, little is known about potential emissions from corrosion protection systems such as organic coatings or galvanic anodes composed of Al and Zn alloys, used to protect offshore structures. In order to assess potential chemical emissions from offshore wind farms and their impact on the marine environment water and sediment were taken in and around offshore wind farms of the German Bight between 12.04.2021 and 23.04.2021 within the context of the Hereon-BSH project OffChEm II. The surface sediment samples were taken by a box grab, homogenized, freeze-dried and wet-sieved to gain the <20 μm grain size fraction. The <20 μm grain size fraction was acid digested and measured by ICP-MS/MS for their (trace) metal mass fractions.